Planning the Most Effective Itinerary for Tourists through the use of Data Analysis - R. Regin; S. Suman Rajest; Shynu T; Steffi. R (Research Parks Publishers, 2023)
In order to provide the most effective scheduling alternatives, data analysis of the information that the customer has provided is performed. The mobile application provides further recommendations, such as a list of all the appropriate sites or areas to visit inside the destination that has been picked, once the intended destination has been specified. In addition, the other significant recommendations concerning the method of transportation, the most efficient routes, the most desirable times, and the expenses associated with them will be automatically offered. Additionally, the Android Studio toolkit and the Google Maps interface are utilised in the process of application creation. Hadoop is used for the analysis of weather data. Hadoop is a Java programming platform and open-source Apache software that is utilised in the distributed world for the purpose of managing the management of enormous data volumes. One of the most significant benefits is the utilisation of the machine learning approach to cost estimation in the budget planning process. Travel plans that are efficient are provided by the intelligent local route as well as the form of transportation. The online application offers a platform that functions as a digital assistant that is intelligent and tailored to the tourists' areas of interest.